2016
DOI: 10.1016/j.cobeha.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Human brain development over the early years

Abstract: Recent studies of the structural and functional development of the human brain over the early years have highlighted the rapid development of brain structures and their interconnectivity. Some regional functional specializations emerge within the first months after birth, while others have a more protracted course of development spanning over the first decade or longer. While some anatomical changes enable the emergence of new functions, evidence also points to the importance of resting state oscillations in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 41 publications
(57 reference statements)
0
19
0
2
Order By: Relevance
“…It is also possible that atypical patterns of brain development play a role in the grey matter volume and fine motor skills relationship, in the preterm brain. 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that atypical patterns of brain development play a role in the grey matter volume and fine motor skills relationship, in the preterm brain. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a less-defined exploration of brain areas known to be associated with VMI is a useful approach, especially when investigating the neural associations of a multi-modal ability, in groups with potentially atypical brain development trajectories. 16 …”
Section: Introductionmentioning
confidence: 99%
“…During these stages, structural brain development consists of increased white matter volume and enhanced functional brain development as measured by functional magnetic resonance imaging. 24 The Chinese Great Famine represents extreme stress because of nutrition deprivation. Findings from the current study suggest that nutrition, stress, or the combination of them both, are more important in these stages.…”
Section: Impact Of Exposure To Famine From Mid-childhood To Early Adumentioning
confidence: 99%
“…It can be assumed that thalamocortical connections are essential for the production of frontal alpha activity (7.5‐12.5 Hz) during sevoflurane anesthesia . In a functional magnetic resonance imaging study in children who were 0, 1, or 2 years old, it was demonstrated that some thalamic functional networks showed a marked development during the first year, with continued strengthening during the second year …”
Section: Discussionmentioning
confidence: 99%